Surgically Relevant Localization of the Central Sulcus With High-Density Somatosensory-Evoked Potentials Compared With Functional Magnetic Resonance Imaging - Lascano, Agustina M.; Grouiller, Frédéric; Genetti, Mélanie; Spinelli, Laurent; Seeck, Margitta; Schaller, Karl; Michel, Christoph M. (Neurosurgery, 2014)
Abstract BACKGROUND: Resection of abnormal brain tissue lying near the sensorimotor cortex entails precise localization of the central sulcus. Mapping of this area is achieved by applying invasive direct cortical electrical stimulation. However, noninvasive methods, particularly functional magnetic resonance imaging (fMRI), are also used. As a supplement to fMRI, localization of somatosensory-evoked potentials (SEPs) recorded with an electroencephalogram (EEG) has been proposed, but has not found its place in clinical practice. OBJECTIVE: To assess localization accuracy of the hand somatosensory cortex with SEP source imaging. METHODS: We applied electrical source imaging in 49 subjects, recorded with high-density EEG (256 channels). We compared it with fMRI in 18 participants and with direct cortical electrical stimulation in 6 epileptic patients. RESULTS: Comparison of SEP source imaging with fMRI indicated differences of 3 to 8 mm, with the exception of the mesial-distal orientation, where variances of up to 20 mm were found. This discrepancy is explained by the fact that the source maximum of the first SEP peak is localized deep in the central sulcus (area 3b), where information initially arrives. Conversely, fMRI showed maximal signal change on the lateral surface of the postcentral gyrus (area 1), where sensory information is integrated later in time. Electrical source imaging and fMRI showed mean Euclidean distances of 13 and 14 mm, respectively, from the contacts where electrocorticography elicited sensory phenomena of the contralateral upper limb. CONCLUSION: SEP source imaging, based on high-density EEG, reliably identifies the depth of the central sulcus. Moreover, it is a simple, flexible, and relatively inexpensive alternative to fMRI.